Pengaruh Konten Influencer di Media Sosial terhadap Tingkat FOMO pada Gen Z (Analisis Studi Literatur) - Mutiara Hakiki; Sri Nada Nadziran; Sri Mulyeni (Jurnal Pendidikan Dirgantara, 2026)
The phenomenon of Fear of Missing Out (FOMO) has become increasingly prominent among Generation Z due to the high intensity of social media use. Social media serves not only as a communication tool but also as a space for identity construction and the pursuit of social validation. Exposure to influencer content portraying ideal lifestyles, social achievements, and trending activities encourages individuals to remain constantly connected in order to avoid feeling left behind in digital communities. This study aims to analyze the influence of social media influencer content on the level of FOMO among Generation Z. The research employs a qualitative descriptive approach using a literature review method by examining relevant national and international academic journals published within the last five years. Data were analyzed by identifying patterns linking influencer content exposure, psychological mechanisms of FOMO, and its impact on Generation Z’s behavior and psychological well-being. The findings indicate that influencer content significantly contributes to social comparison processes and increases the need for digital validation, such as likes and comments, which are perceived as indicators of social acceptance. This condition strengthens FOMO tendencies and leads to excessive digital engagement, consumptive behavior, and psychological pressure. The discussion highlights that social media algorithms further intensify this cycle by repeatedly promoting popular and viral content. In conclusion, influencer content plays a crucial role in intensifying FOMO among Generation Z, emphasizing the importance of digital literacy and critical awareness to mitigate its negative effects.